Mobile and Wireless Technology 2018 International Conference on Mobile and Wireless Technology (ICMWT 2018) - Kim, Kuinam J.; Kim, Hyuncheol; SpringerLink (Online service) (Singapore : Springer Nature Singapore : Imprint: Springer, 2019)
This book presents peer-reviewed contributions from the 5th International Conference on Mobile and Wireless Technology (ICMWT 2018), held June 25-27, 2018 in Hong Kong. This conference provided researchers and practitioners from both academia and industry with a platform to keep them abreast of cutting-edge developments in the field. The book includes papers on mobile and wireless networks and their applications, the increasingly important security issues relating to mobile and wireless systems, data management, as well as the latest developments in mobile software development, and multimedia and wireless communications.
Track 1. Mobile and Wireless Technology -- Track 2. Technology of AI and IoT with Wireless and Advanced Networking -- Track 3. Applications.
Keywords: Telecommunication; Computer engineering; Computer networks .; Signal processing; Communications Engineering, Networks; Computer Engineering and Networks; Signal, Speech and Image Processing